2015
DOI: 10.1016/j.ibmb.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution and expression of the CRAL_TRIO protein family in insects

Abstract: a b s t r a c t CRAL_TRIO domain proteins are known to bind small lipophilic molecules such as retinal, inositol and Vitamin E and include such gene family members as PINTA, a-tocopherol transfer (ATT) proteins, retinoid binding proteins, and clavesins. In insects, very little is known about either the molecular evolution of this family of proteins or their ligand specificity. Here we characterize insect CRAL_TRIO domain proteins and present the first insect CRAL_TRIO protein phylogeny constructed by performin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…We also investigated the reference genome to search for any CRAL-TRIO domain genes that may be found in the genome but not expressed in the tissues we sampled. We found support for the expansion of the CRAL-TRIO domain gene family in butterflies by identifying 43 CRAL-TRIO domain genes in the H. melpomene genome comparable with the 42 found in Manduca sexta ( Smith and Briscoe 2015 ). We also investigated 18 resequenced H. melpomene genomes ( Martin et al 2013 ) for structural variation (specifically CNV) and found that 32 of the 43 genes in the reference genome had either a large duplication or deletion in at least one of the resequenced genomes.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…We also investigated the reference genome to search for any CRAL-TRIO domain genes that may be found in the genome but not expressed in the tissues we sampled. We found support for the expansion of the CRAL-TRIO domain gene family in butterflies by identifying 43 CRAL-TRIO domain genes in the H. melpomene genome comparable with the 42 found in Manduca sexta ( Smith and Briscoe 2015 ). We also investigated 18 resequenced H. melpomene genomes ( Martin et al 2013 ) for structural variation (specifically CNV) and found that 32 of the 43 genes in the reference genome had either a large duplication or deletion in at least one of the resequenced genomes.…”
Section: Introductionsupporting
confidence: 52%
“…The CRAL-TRIO domain gene family is another family that is evolving by lineage-specific duplication in insects and has undergone an expansion in Lepidoptera (moths and butterflies; Smith and Briscoe 2015 ). Lepidoptera thus have almost twice as many CRAL-TRIO domain genes relative to other insects ( Smith and Briscoe 2015 ). The lineage-specific duplications of this gene family make it a candidate to study for CNV ( Zhang 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recent research [31] indicates that Sec14 proteins are essential in membrane trafficking, connecting lipid metabolism with phosphoinositide signaling through transport of phosphatidylinositol. Sec14 proteins contain a CRAL-TRIO lipid-binding domain, and protein families with this domain also show expansion in lepidopteran species [32]. However, the number of Sec14 proteins in both the F. candida genome and the genome of a related collembolan, O. cincta , exceeds by far the greatest number observed in any hexapod genome (Additional file 1).…”
Section: Resultsmentioning
confidence: 99%
“…PINTA , which binds the visual chromophore in Drosophila eyes, appears to be missing in Lepidoptera; however, the M. sexta genome encodes 42 other CRAL-TRIO domain-containing proteins (GenBank Accession Nos. KT943537-KT943566) (Smith and Briscoe, 2015), far more than other insect genomes examined ( D. melanogaster , n = 12; A. gambiae , n = 14; T castaneum , n = 18). Many of the genes in this family have duplicated within Lepidoptera.…”
Section: Resultsmentioning
confidence: 99%